Morphological Variations of Sigmoid Notch Using Orthopantomogram among Patient Reporting at Sandeman Provincial Hospital, Quetta - Syed Ahsan Ali, Nasrullah Mengal, Zaid Ali, Jiand Malik Baloch, Summya Waseem, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the Morphological variations of sigmoid notch using orthopantomogram in adult patients Study design: Cross sectional study Place and duration of study: Department of Orthodontics, Dental Section, Sandeman Provincial Hospital, Quetta, from June 2020 to December 2020. Material and methods: All the adult patients who fulfilled inclusion criteria were included in this research project after screening according to selection criteria.200 candidates were included and underwent Orthopantomogram for evaluation of morphological variations of sigmoid notch. Reports were assessed and morphological variations were noted. Data was analyzed by using SPSS. ver.20. Results: The mean age of candidates was 25.5 ± 5 years. There were 129 (64.5%) male candidates and 71 (35.5%) were female candidates. The males to female ratio was 1.8:1. Out of 200 candidates, left side was involved in 100 (50%) candidates and right side was involved in 100 (50%) candidates. Out of 200 cases, wide sigmoid notch was observed in 115 (57.5%) candidates, sloping sigmoid notch was observed in 59 (29.5%) candidates and round sigmoid notch was observed in 26 (13.0%) candidates. Conclusion: In our study, we observed the most common sigmoid notch shape was observed to be wide type followed by sloping type. Keywords: Morphology, Variations, Sigmoid notch, Orthopantomogram, Orthodontics